The provision of cell phones as a recruitment and retention strategy for people who inject drugs enrolling in a randomized trial. (1st March 2018) - Stewart, Catherine; Kopinski, Hannah; Liebschutz, Jane; Holmdahl, Inga; Keosaian, Julia; Herman, Debra; Anderson, Bradley; Stein, Michael
Highlights: Examined cell phones as compensation for injection drug using participants. Cell phones as compensation allowed inclusion of otherwise ineligible participants. May improve generalizability through recruitment of a more vulnerable subgroup. The cell phone and gift card compensation groups were retained at similar rates. Cell phone compensation may improve recruitment/retention in transient populations. Abstract: Background: Studies of drug-using populations often restrict enrollment by limiting participation to those with a working telephone. It is unknown whether supplying phones could broaden recruitment and sustain retention among an urban population of people who inject drugs (PWID). We compare the feasibility of offering pay-by-month phones to gift card compensation as part of an ongoing randomized controlled trial of hospitalized PWID. Methods: Participants were recruited from inpatient services at an urban hospital in Boston, MA to participate in an ongoing randomized trial testing a motivational interviewing (MI) intervention. Participants who did not have their own phone at the time of enrollment were offered a pay-by-month phones as compensation for study participation. Results: Eighty-one participants met study criteria, were enrolled, and completed the study at the time of analysis. We used a generalized estimating equation to compare the overall likelihood of attending interviews during the 12-month follow-up period. Participants receiving phones tended to have lower mean educational attainment (11.4 years vs. 12.1 years), were significantly (Fisher's exact p < 0.001) more likely to report homelessness during the past 90 days (86.7% vs. 37.3%), and were significantly less likely (Fisher's exact p = .044) to be employed (3.3% vs. 20.4%) compared to those receiving gift cards. Participants in each group were equally likely to attend follow-up interviews during the study (83.3% vs. 88.3%, p = 0.53). Conclusion: Offering phones as a compensation method allows recruitment of a more disenfranchised population without impacting study retention and therefore may improve generalizability of study results.